Organosulfur Compounds: A Review of Their Anti-inflammatory Effects in Human Health - Ruhee, Ruheea Taskin; Roberts, Llion Arwyn; Ma, Sihui; Suzuki, Katsuhiko (Frontiers in Nutrition, 2020)
Phytochemicals, or phytoprotectants are usually not considered as essential nutrients, but they arewidely recognized for providing protective human health benefits. Among the phytoprotectants, epidemiological and experimental studies show that dietary organosulfur compounds (OSC) play a significant role in preventing various human pathological progressions, including chronic inflammation, by decreasing inflammatory mediators such as nitric oxide (NO), prostaglandin (PG) E2, interleukin (IL)-1β, IL-6, tumor necrosis factor (TNF)-α and IL-17, which are all typical hallmarks of inflammation. Evidence supports OSC in reducing the expression of these markers, thereby attenuating chronic inflammatory processes. Nuclear factor-kappa B (NF-κB) is a key regulating factor during inflammation, and novel evidence shows that OSC downregulates this transcriptional factor, thus contributing to the anti-inflammatory response. In vitro and in vivo studies show that inflammation is mechanistically linked with acute and chronic pathological conditions including cancer, diabetes, obesity, neural dysfunction etc. Furthermore, a considerable number of experiments demonstrate that the anti-inflammatory properties of OSC occur in a dose-dependent manner, and highlight indirect mechanisms as well as potent co-functions for protective roles as antioxidants, and in providing chemoprotection and neuroprotection. In this brief review, we provided an overview of the anti inflammatory effects of OSC, and elucidated probable mechanisms that are associated with inflammation and chronic disorders.